Impact Assessment of Climate Change on Storm Surge and Sea Level Rise Around Viti Levu, Fiji - Sabūnas, Audrius; Mori, Nobuhito; Fukui, Nobuki; Miyashita, Takuya; Shimura, Tomoya (Frontiers in Climate, 2020)
Projecting the sea level rise (SLR), storm surges, and related inundation in the Pacific Islands due to climate change is important for assessing the impact of climate change on coastal regions as well as the adaptation of the coastal regions. The compounding effects of storm surges and SLR are one of the major causes of flooding and extreme events; however, a quantitative impact assessment that considers the topographical features of the island have not been properly conducted. Therefore, this study projects the impact of storm surge and SLR due to climate change on Viti Levu, which is the biggest and most populous island in Fiji. The impact of SLR on the inundation in coastal areas was simulated using a dynamic model based on the IPCC SROCC scenarios and the 1/100 years return period storm surge implemented based on the RCP8.5 equivalent scenario. The affected inundation area and population due to storm surges and SLRs are discussed based on the compound effects of SLR and storm surge. Although the contribution of SLR to the inundation area was quite significant, the 1/100 year storm surge increased by 10% to 50% of the inundation area. In addition, a narrow and shallow bay with a flat land area had the largest impact of storm surge inundation. Furthermore, the western wind direction had the most severe storm surge inundation and related population exposure due to the topographic and bathymetric characteristics of Viti Levu Island.